Manajemen Krisis Hotel Aston Kartika Grogol - Farraas Muhammad Hendroyono; Neni Yulianita (Bandung Conference Series: Public Relations, 2022)
Abstract. This research discusses the crisis management of Aston Kartika Grogol Hotel, especially the role of Public Relations of Aston Kartika Grogol Hotel in dealing with the decrease in the number of visitors during the ‘New Normal’ Covid-19 period. As is well known, the Covid-19 pandemic began to plague Indonesia since March 2020. Based on direct directions from the Government of Republic Indonesia regarding breaking the covid-19 chain, which is increasingly spreading day after day, it is determined that every citizen to stay in their respective homes and carry out self quarantine. In order to comply with these government regulations, Aston Kartika Grogol Hotel is commited to carrying out a temporary closure of operations starting from April 1, 2020 until re-opening in June 2020. With the enactment of government regulations regarding the temporary closure of activities, the hotel business is one of the sectors affected by the crisis, many activities were canceled and had to lay off a number of employees. Hotel business people are required to rack their brains so that somehow the business continues to run even in the midst of the Covid-19 pandemic crisis. This study uses a qualitative research method with a descriptive analytical approach. Data collection methods used include interviews, observation and literature study. The purpose of this research is to study and analyze the role of Public Relations at Aston Kartika Grogol Hotel, crisis management strategies, and the role of media relations. By using analysis techniques and source triangulation. The results of this study found that the PR Manager carried out the operational stages of PR including, fact finding, planning and programming, taking action and communicating, and evaluating the program. In increasing public trust the PR Manager designed and enforced a fairly strict health protocol. Then do the exposure one of them through social media. Media Relations Hotel Aston Kartika Grogol plays a role in increasing visitor interest, so that publicity activities regarding news programs that are being implemented and require the dissemination of information widely to the public are carried out. Abstrak. Penelitian ini membahas mengenai manajemen krisis Hotel Aston Kartika Grogol khususnya peran Public Relations Hotel Aston Kartika Grogol dalam menangani penurunan jumlah pengunjung di masa ‘New Normal’ Covid-19. Seperti yang diketahui, pandemi Covid-19 mulai mewabah di Indonesia sejak bulan Maret 2020. Berdasarkan arahan langsung dari Pemerintahan Republik Indonesia terkait memutus mata rantai covid-19 yang semakin hari penyebarannya semakin tinggi maka ditetapkan agar setiap warga negara untuk tetap tinggal dirumah masing-masing dan melakukan karantina mandiri. Demi menaati peraturan pemerintah tersebut, Hotel Aston Kartika Grogol berkomitmen untuk melakukan penutupan operasional sementara terhitung dari tanggal 1 April 2020 sampai kembali dibuka pada bulan Juni 2020. Dengan diberlakukannya peraturan pemerintah mengenai penutupan aktivitas sementara tersebut membuat bisnis perhotelan menjadi salah satu sektor yang terdampak krisis karena banyaknya kegiatan yang dibatalkan hingga harus merumahkan sejumlah karyawannya. Para pelaku bisnis hotel dituntut untuk memutar otak agar bagaimana pun caranya bisnis tetap berjalan meskipun ditengah krisis pandemi covid-19. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif analitis. Metode pengumpulan data yang digunakan meliputi wawancara, observasi, dan studi pustaka. Tujuan dari penelitian ini yaitu untuk mengkaji dan menganalisa peran Public Relations Hotel Aston Kartika Grogol, strategi manajemen krisis, dan peran media relations. Dengan menggunakan teknik analisis dan triangulasi sumber. Hasil penelitian ini ditemukan bahwa PR Manager melakukan tahapan operasional PR meliputi, fact finding, planning and programming, taking action and communicating, dan evaluating the program. Dalam meningkatkan kepercayaan publik PR Manager merancang dan memberlakukan protokol kesehatan yang cukup ketat. Kemudian dilakukannya exposure salahsatunya melalui media sosial. Media Relations Hotel Aston Kartika Grogol berperan dalam meningkatkan minat pengunjung, Sehingga aktivitas publisitas mengenai pemberitaan program yang sedang dilaksanakan dan membutuhkan penyebaran informasi secara luas kepada publik terjalankan.